Problemy demograficzne regionu jeleniogórskiego - Maciejuk, Marian (Demographic Problems of Jelenia Góra Region, 2007)
The hereby article presents an analysis of problems in population development of Jelenia Góra between 1995 and 2004. The research covered changes in number and structure of population according to sex and age. The analysis concentrates in particular on the factors of population development, i.e. natural movement covering births, deaths, natural growth, marriages, internal and external migratory movement expressed in migration balance. The research concentrates on cause-result analysis of occurred problems at the background of social and political situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 151-164